المعاش النفسي لدى المرأة المتكررة الإجهاض دراسة حالات بالمؤسسة الاستشفائية المتخصصة في طب النساء والتوليد سليمان عميرات المسيلة - لكحل فيروز; اشراف: خرخاش اسماء (جامعة محمد بوضياف المسيلة, 2025)
هدفت هذه الدراسةلتعرف على المعاش النفسي للمرأة متكررة الإجهاض باستعمال منهج العيادي الذي يعتمد على دراسة حالة حيث تمت دراسة ثلاث حالات تعرضوا إلىلإجهاض المتكرر ولقد استعملت في هذه الدراسة الأدوات التالية: المقابلة النصف الموجهة والملاحظة ومقياس إجهاد الصدمة المنقح ومقياس الاكتئاب ل بيك ومقياس قلق الموت. وقد خلصت النتائج: - أن كل الحالات تعاني من ضغط ما بعد الصدمة. - أن كل الحالات تعاني من اكتئاب شديد ماعدا الحالة الثانية تعاني من اكتئاب شديد جدا وهذا ما قد يرجع إلى أنها لا تتلقى الدعم والمساندة من طرف عائلة زوجها لا بل حتى زوجها يلومها ويحملها المسؤولية. - أن كل الحالات تعاني من مستوى قلق الموت مرتفع. من خلال هذه الدراسة نستشف المعاناة النفسية لهذه الفئة والتي لا بد من القيام بدراسة تعمل على وضع خطط كفالة نفسية وعلاجية. كلمات المفتاحية: اضطراب الضغط ما بعد الصدمة، الاكتئاب، قلق الموت، المرأة المتكررة الإجهاض Studysummary: This study aimed to identify the psychological well-being of women who have had recurrent miscarriages using a clinical approach that relies on a case study in which three cases who had had recurrent miscarriages were studied. The following tools were used in this study: semi-directed interview, observation, the revised traumatic stress scale, the Beck depression scale, and an anxiety scale. death. The results were concluded: - All cases suffer from post-traumatic stress. - All cases suffer from severe depression, except for the second case, who suffers from very severe depression, and this may be due to the fact that she does not receive support and support from her husband’s family. In fact, even her husband blames her and holds her responsible. - All cases suffer from a high level of death anxiety. Through this study, we discover the psychological suffering of this group, which requires a study to develop psychological and therapeutic care plans. Keywords: Post-traumatic stress disorder, depression, death anxiety, repeated miscarriage.